One Year Genome Evolution of Lausannevirus in Allopatric versus Sympatric Conditions. (19th May 2017) - Mueller, Linda; Bertelli, Claire; Pillonel, Trestan; Salamin, Nicolas; Greub, Gilbert
Abstract: Amoeba-resisting microorganisms raised a great interest during the last decade. Among them, some large DNA viruses present huge genomes up to 2.5 Mb long, exceeding the size of small bacterial genomes. The rate of genome evolution in terms of mutation, deletion, and gene acquisition in these genomes is yet unknown. Given the suspected high plasticity of viral genomes, the microevolution of the 346 kb genome of Lausannevirus, a member of Megavirales, was studied. Hence, Lausannevirus was co-cultured within the amoeba Acanthamoeba castellanii over one year. Despite a low number of mutations, the virus showed a genome reduction of 3.7% after 12 months. Lausannevirus genome evolution in sympatric conditions was investigated by its co-culture with Estrella lausannensis, an obligate intracellular bacterium, in the amoeba A. castellanii during one year. Cultures were split every 3 months. Genome sequencing revealed that in these conditions both, Lausannevirus and E. lausannensis, show stable genome, presenting no major rearrangement. In fact, after one year they acquired from 2 to 7 and from 4 to 10 mutations per culture for Lausannevirus and E. lausannensis, respectively. Interestingly, different mutations in the endonuclease encoding genes of Lausannevirus were observed in different subcultures, highlighting the importance of this gene product in the replication of Lausannevirus. Conversely, mutations in E. lausannensis were mainly located in a gene encoding for a phosphoenolpyruvate–protein phosphotransferase (PtsI), implicated in sugar metabolism. Moreover, in our conditions and with our analyses we detected no horizontal gene transfer during one year of co-culture.